Specialized agility abilities of elite table tennis players in different age groups - Liew, E.; Wu, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Table tennis (TT) is characterized by its rapid and dynamic nature, highlighting the critical importance of agility for players in its sporting discipline [1]. Consequently, the main purpose of this study is to employ the TT-specific agility test to assess the lower limb agility capabilities of elite male TT players within distinct age groups (i.e., college and U16). Moreover, agility encompasses both motor and cognitive abilities, including inhibitory control [2], which aids in maintaining focus on the assigned task and preventing impulsive actions that may potentially lead to errors. This attribute is considered indispensable in executing nimble movements [3]. Thus, the secondary objective of this study is to quantify the correlation between these two variables. We hypothesize that the college group will demonstrate superior performance in both assessments, as well as stronger inhibitory control, thus corresponding to a greater agility capacity. METHODS: Twenty-nine Taiwanese TT players were recruited as participants and divided into two groups: college (n=14, average age 20.07±1.89; height 172.57 ± 5.60; weight 67.07 ± 8.63; BMI 22.45 ± 2.18) and U16 (n=15, average age 14.27±0.96; height 172.02 ± 6.88; weight 58.56 ± 8.52; BMI 19.75 ± 2.42). The TT-Agility Test (TTAT) was used to assess agility, and the Covert Orienting of Visuo-spatial Attention Tasks (COVAT) was used to assess inhibitory control ability of the lower limb. Independent samples t-tests were used to analyze the difference between groups, and Pearson correlation was used to measure the linear relationship between TTAT and COVAT. RESULTS: We found that the college group performed better than the U16 group in TTAT (p < .001) but not in COVAT. Correlation analysis between TTAT and COVAT did not show significant differences. CONCLUSION: The findings demonstrate that collegiate TT players possess notably superior agility capabilities specific to the sport when compared to U16 players. Conversely, traditional inhibitory control tests, such as COVAT, prove to be insufficient in discerning discrepancies among TT players across different age groups. Therefore, there is a need for the development of more tailored assessment tools for sport-specific inhibitory control. Although no significant differences were observed in the correlation analysis between TTAT and COVAT, it can be inferred that enhanced agility is likely accompanied by improved inhibitory control abilities.